PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V MIN 1 KOTA MAKASSAR - Fatmawati Fatmawati; Muhammad Yahdi; Andi Halimah (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to study the use of Student Worksheets (LKPD) in Indonesian subjects,Indonesian language learning outcomes using LKPD, and the use of LKPD for the use ofgrade 1 learning outcomes in Makassar City.This research uses ex post facto research. The populationin this study amounted to 30 students. The sampling technique was carried out by using a purposivesampling. The instruments used in this research are questionnaires and documentation. The data was thenanalysed using descriptive and inferential analysis. Based on the results of data analysis usingdescriptive tests, it can be concluded that the results of the questionnaire regarding the use ofLKPD in learning Indonesian can be done by students in the moderate category by 60% or 18people, including in the high category. responded by 26.7% or 9 people and in the low categorywere 13.3% or 4 students. Learning outcomes of students who use LKPD in learningIndonesian in the medium category are 60% or 18 people, the high category is 30% or 9 peopleand in the low category is 10% or 3 students. If it is categorized in the mastery of learning, it isobtained in the medium category. Based on the results of simple regression analysis on the twovariables using LKPD and student learning outcomes that there is a significant and positive effect. Themagnitude of the effect is 27.7%, with the correlation coefficient between the use of LKPD and studentlearning outcomes is positive between the use of LKPD and student learning outcomes. If the use of LKPDis increased, it will help improve student learning outcomes.